Auxin efflux carrier PsPIN4 identified through genome-wide analysis as vital factor of petal abscission - Sun, Yin; Chen, Junqiang; Yuan, Yanchao; Jiang, Nannan; Liu, Chunying; Zhang, Yuxi; Mao, Xiuhong; Zhang, Qian; Fang, Yifu; Sun, Zhenyuan; Gai, Shupeng (Frontiers in Plant Science, 2024)
PIN-FORMED (PIN) proteins, which function as efflux transporters, play many crucial roles in the polar transportation of auxin within plants. In this study, the exogenous applications of auxin IAA and TIBA were found to significantly prolong and shorten the florescence of tree peony (Paeonia suffruticosa Andr.) flowers. This finding suggests that auxin has some regulatory influence in petal senescence and abscission. Further analysis revealed a total of 8 PsPINs distributed across three chromosomes, which could be categorized into two classes based on phylogenetic and structural analysis. PsPIN1, PsPIN2a-b, and PsPIN4 were separated into the “long” PIN category, while PsPIN5, PsPIN6a-b, and PsPIN8 belonged to the “short” one. Additionally, the cis-regulatory elements of PsPIN promoters were associated with plant development, phytohormones, and environmental stress. These genes displayed tissue-specific expression, and phosphorylation sites were abundant throughout the protein family. Notably, PsPIN4 displayed distinct and elevated expression levels in roots, leaves, and flower organs. Expression patterns among the abscission zone (AZ) and adjacent areas during various flowering stages and IAA treatment indicate that PsPIN4 likely influences the initiation of peony petal abscission. The PsPIN4 protein was observed to be co-localized on both the plasma membrane and the cell nucleus. The ectopic expression of PsPIN4 reversed the premature flower organs abscission in the Atpin4 and significantly protracted florescence when introduced to Col Arabidopsis. Our findings established a strong basis for further investigation of PIN gene biological functions, particularly concerning intrinsic relationship between PIN-mediated auxin polar